Comparative analysis of the strength of restoration polymers of light polymerization for dental restoration using the acoustic emission method: part one - Кухта , Віктор Степанович; Макєєв , Валентин Федорович; Кирманов , Олександр Сергійович; Ключковська , Наталія Романівна; Скальський , Валентин Романович; Станкевич , Олена Михайлівна (Actual Dentistry, 2021)
Purpose. Comparative analysis of the strength of hybrid restoration composites of light polymerization during their local loading using the phenomenon of acoustic emission. The following restoration composites were studied: Latelux, Tetric N-Ceram, Charisma Classic. Results. It was determined that the nature of the destruction of all composites is the same: elastic-plastic at the initial stage of the load with a transition to brittle as its further growth. Three types of composite failure are observed: correct, incorrect and mixed. The first predominated during fracture under the action of local loading of the Latelux composite, for Tetric N-Ceram and Charisma Classic materials a mixed type of fracture is characteristic. Conclusions. Analysis of the parameters of the AE signals showed that the signals had the highest amplitude and energy when the Tetric N-Ceram composite was destroyed, and the lowest – Latelux. All dental composites are dominated by high-energy ductile-brittle and brittle fracture, which indicates the spread of micro- and macrocracks of various sizes in materials. Key words: polymer composites, strength, acoustic emission method.